Β Thromboglobulin and platelet factor 4 in bronchoalveolar lavage fluid of patients with systemic sclerosis. Issue 3 (11th February 2005) - Kowal-Bielecka, O; Kowal, K; Lewszuk, A; Bodzenta-Lukaszyk, A; Walecki, J; Sierakowski, S
Abstract : Objective: To evaluate concentrations of the platelet activation markers β thromboglobulin (BTG) and platelet factor 4 (PF4) in bronchoalveolar lavage fluid (BALF) from patients with systemic sclerosis with and without scleroderma interstitial lung disease (SLD). Methods: BTG and PF-4 were measured by enzyme immunoassay in BALF from 37 patients with systemic sclerosis. Controls were 10 healthy subjects. BALF was collected during routine bronchoscopy from the right middle lobe. SLD was diagnosed by high resolution computed tomography of the lungs. Results: BTG was detected in 11 of the patients with systemic sclerosis (29.7%) and PF4 was found in eight (21.6%). Mean (SD) concentrations of BTG and PF4 in BALF from patients with detectable levels of these platelet activation markers were 106.9 (69.8) and 35.2 (17.4) IU/ml, respectively. The BTG:PF4 ratio was more than 2:1, indicating in vivo release. Both markers were found exclusively in patients with SLD. SLD patients with detectable platelet activation markers had a significantly shorter disease duration than those with undetectable BTG/PF4. Conclusions: The study provides evidence that activation of blood platelets takes place within the lungs of patients with SLD and may contribute to the development of lung fibrosis.